The Demand for Housing: A Study in Specification and Grouping - Polinsky, A. Mitchell (Econometrica, 1977)
The low estimates of the income elasticity of housing demand obtained when individual households are the unit of observation are theoretically reconciled with the high estimates obtained when metropolitan-wide averages are used. The omission of the housing price term biases the ungrouped (whether stratified by metropolitan areas or not) estimate(s) downward and the grouped estimate upward. The inclusion of a metropolitan-wide average housing price term worsens the downward bias of the unstratified ungrouped estimate. The corresponding price elasticity estimate is biased upward (toward zero). These results are interpreted in terms of the theory of residential location and used to explain the empirical evidence. For the evidence considered, the true income and price elasticities are approximately .75 and -.75, respectively.